(y-z-b)-(b+y+z)=

Simple and best practice solution for (y-z-b)-(b+y+z)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y-z-b)-(b+y+z)= equation:


Simplifying
(y + -1z + -1b) + -1(b + y + z) = 0

Reorder the terms:
(-1b + y + -1z) + -1(b + y + z) = 0

Remove parenthesis around (-1b + y + -1z)
-1b + y + -1z + -1(b + y + z) = 0
-1b + y + -1z + (b * -1 + y * -1 + z * -1) = 0
-1b + y + -1z + (-1b + -1y + -1z) = 0

Reorder the terms:
-1b + -1b + y + -1y + -1z + -1z = 0

Combine like terms: -1b + -1b = -2b
-2b + y + -1y + -1z + -1z = 0

Combine like terms: y + -1y = 0
-2b + 0 + -1z + -1z = 0
-2b + -1z + -1z = 0

Combine like terms: -1z + -1z = -2z
-2b + -2z = 0

Solving
-2b + -2z = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '2z' to each side of the equation.
-2b + -2z + 2z = 0 + 2z

Combine like terms: -2z + 2z = 0
-2b + 0 = 0 + 2z
-2b = 0 + 2z
Remove the zero:
-2b = 2z

Divide each side by '-2'.
b = -1z

Simplifying
b = -1z

See similar equations:

| (7262x)+(1.26a)-(2844x-8.23a)= | | 2x^5+7x^4-10x^3-53x^2-28x+28= | | (72.62x)+(1.26a)-(2844x-8.23a)= | | 8(2x-9)=2(8x+6) | | 3x^3=32 | | 9+11z-3=5z+69-3z | | -3(x-1)-7=4x-11 | | 18+3y=9y | | (24.2x)+(8.25)+(83.6x-2.92)= | | 4x=28-0.25(4-16x) | | 5n-6(n+2)=14 | | -8(3x-4)+1=15 | | 5s+3s=56 | | (2x+6a)-(4x-a)= | | 8x=14-0.5(10x+2) | | 2z=-10 | | 61=16+5(x-3) | | 4.2q-5.9-5.5q=-2.3q-3.6 | | 8p=2(p+9) | | 8(w-2)= | | 100.39=28.90+49.99+2x | | (2x+5)+(x-2)= | | a+(a+450000)=625000000 | | 38.5=2x-1.5+2x-1.5+x+x+x+7.2 | | 33.9ab-82.4ac+29.3ad-84.8ac+73.2ab= | | y-17=-33 | | 2x-20=36.37 | | 9.9x+38.57=-10.1+38.41b | | 108=x+x+3.5x+3.5x | | Y^2+2y-24=0 | | 66.8=2x+4.7+2x+4.7+2x+4.7+2x+4.7 | | (c-3)(c-3)=o |

Equations solver categories